Daily commuting in the Bratislava metropolitan area: case study with mobile positioning data. (2nd October 2018) - Šveda, Martin; Barlík, Peter
Abstract: Suburban development in the metropolitan area of Bratislava (Slovakia) led to an unprecedented redistribution of population. As the majority of suburbanized families are car-dependent, the influx of new residents is a major source of growing traffic problems. However, due to the unwillingness of suburban in-migrants to change their registration (approximately 100, 000 unregistered residents), the commuting based on the census data is insufficient to capture the real pattern of daily mobility in the hinterland of Bratislava. Yet, mobile positioning data represent a powerful source of information with high spatial accuracy and endless options for use. The objective of this study is to analyze mobility patterns of commuting in the Bratislava metropolitan area using mobile positioning data. The experiment was carried out in September 2017 over a fourteen-day period with a sample of 191, 404 mobile phone users. The key task was to find a suitable methodological approach to extract useful information of human mobility patterns. We used the concept of anchor points, which represent main nodes of human activity and space–time trajectories. Extracting the localization of "work" and "sleep" we modeled the origin-destination matrix of daily commuting with a spatial accuracy not available until now.